Hemaglobinopathy and Pregnancy Outcomes: A Historical Cohort Study - Liu, Song (Université d'Ottawa / University of Ottawa, 2012)
Pregnancy in women with hemoglobinopathy has been associated with an increased risk of adverse pregnancy outcomes. We conducted a historical cohort study using Discharge Abstract Database for the fiscal year 1991-1992 through 2007-2008. We estimated the frequency of pregnant women with hemoglobinopathy and examined their associations with adverse pregnancy outcomes. Women with sickle cell disease are more likely to develop pre-eclampsia and preterm labor, and to undergo cesarean delivery than women with nutritional deficiency anemia, suggesting that there are other mechanisms beyond anemia that may be responsible for an increased risk of adverse pregnancy outcomes. The data suggested a synergistic effect of hemoglobinopathy and pre-eclampsia on preterm labor and cesarean delivery. Prediction models for pre-eclampsia, preterm labor and cesarean delivery were created and internally validated for women with hemoglobinopathy, with satisfactory discrimination and calibration.
Keywords: Hemaglobinopathy; sickle cell disease; thalassemia; pregnancy outcomes; pre-eclampsia; preterm labor; cesarean delivery